Anesthetic Management of Charcot-Marie-Tooth Disease - MD, Jae Won Kim; MD, Jin Ho Choi; MD, Goo Kim; MD, Keon Hee Ryu; PhD; Park, Sun Gyoo; MD; PhD; MD, Chang Young Jeong; PhD; et al. (Archives of Clinical and Medical Case Reports, 2020)
Charcot-Marie-Tooth (CMT) disease, which is the most common inherited neuropathy, is also referred to as hereditary motor and sensory neuropathy (HMSN) and shows a genetically heterogeneous pattern. CMT is diagnosed mostly by a neurologic specialist. It can be divided into autosomal dominant, autosomal recessive, or X-linked type, based on the transmission pattern. It can also be divided demyelinating or axonal type, based on the electrophysiological findings. Therefore, it is practically not feasible for anesthesiologists to make the diagnosis, and diagnosis becomes even more difficult with the continued emergence of subtypes with the identification of new genes. Moreover, each type has a different phenotype, and each may be managed slightly differently based on the actual symptoms presented. For each case, there are conflicting opinions on the methods for anesthetic management, causing much confusion. Accordingly, in this review, we aimed to discuss the diagnostic methods, types, and treatment methods for CMT from an anesthetic perspective and to review anesthetic management.